Small Animal Look-Locker Inversion Recovery (SALLI) for Simultaneous Generation of Cardiac T1 Maps and Cine and Inversion Recovery–prepared Images at High Heart Rates: Initial Experience - Messroghli, Daniel R.; Nordmeyer, Sarah; Buehrer, Martin; Kozerke, Sebastian; Dietrich, Thore; Kaschina, Elena; Becher, Peter M.; Hucko, Thomas; Berger, Felix; Klein, Christoph; Kuehne, Titus (Radiology, 2011)
To develop a single magnetic resonance (MR) imaging approach for comprehensive assessment of cardiac function and tissue properties in small animals with high heart rates. All animal studies were approved by the local animal care committee. Small animal Look-Locker inversion recovery (SALLI) was implemented on a clinical 3.0-T MR unit equipped with a 70-mm solenoid coil. SALLI combines a segmented, electrocardiographically gated, inversion recovery-prepared Look-Locker-type pulse sequence with a multimodal reconstruction framework. Temporal undersampling and radial nonbalanced steady-state free precession enabled acceleration of data acquisition and reduction of motion artifacts, respectively. Nine agarose gel phantoms were used to investigate different sequence settings. For in vivo studies, 10 Sprague-Dawley rats were evaluated to establish normal T1 values before and after injection of gadopentetate dimeglumine. Seven rats with surgically induced acute myocardial infarction were examined to test the feasibility of detecting myocardial injury. In vitro T1 behavior was studied with linear regression analysis, and in vivo T1 differences between infarcted and remote areas were tested by using the Wilcoxon signed rank test. Phantom studies demonstrated systematic behavior of the T1 measurements, and T1 error could be reduced to 1.3% ± 7.4 by using a simple linear correction algorithm. The pre- and postcontrast T1 of myocardium and blood showed narrow normal ranges. In the area of infarction, SALLI demonstrated hypokinesia (on cine images), myocardial edema (on precontrast T1 maps), and myocardial necrosis (on postcontrast T1 maps and late gadolinium enhancement images). An MR imaging method enabling simultaneous generation of cardiac T1 maps and cine and inversion recovery-prepared images at high heart rates is presented. SALLI allows for simultaneous and time-efficient assessment of cardiac T1 behavior, function, and late gadolinium enhancement at high heart rates.